2017
DOI: 10.1103/physrevb.95.195159
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-vacancy driven electron localization and itinerancy in rutile-based TiO2

Abstract: Oxygen-deficient TiO2 in the rutile structure as well as the Ti3O5 Magnéli phase is investigated within the charge self-consistent combination of density functional theory (DFT) with dynamical mean-field theory (DMFT). It is shown that an isolated oxygen vacancy (VO) in titanium dioxide is not sufficient to metallize the system at low temperatures. In a semiconducting phase, an ingap state is identified at ε IG ∼ −0.75 eV in excellent agreement with experimental data. Bandlike impurity levels, resulting from a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 85 publications
1
21
0
Order By: Relevance
“…Figure 1 shows the pDOS patterns of pure and single O-vacancy of anatase and rutile structures, which clearly represented the main contribution of O 2p and Ti 3d orbitals in the valance and conduction bands, respectively. This was in a close agreement with previous results [38][39][40][41], for the defect states of anatase and rutile. The band gap, regardless of defect states, increased by generation of oxygen defect from 3 to 3.4 eV in rutile, and from 3.2 to 3.6 eV in anatase structures, similar to our previous study [43].…”
Section: O-vacancy In the Bulk Structure Of Rutile And Anatasesupporting
confidence: 93%
See 1 more Smart Citation
“…Figure 1 shows the pDOS patterns of pure and single O-vacancy of anatase and rutile structures, which clearly represented the main contribution of O 2p and Ti 3d orbitals in the valance and conduction bands, respectively. This was in a close agreement with previous results [38][39][40][41], for the defect states of anatase and rutile. The band gap, regardless of defect states, increased by generation of oxygen defect from 3 to 3.4 eV in rutile, and from 3.2 to 3.6 eV in anatase structures, similar to our previous study [43].…”
Section: O-vacancy In the Bulk Structure Of Rutile And Anatasesupporting
confidence: 93%
“…Theory has also shown that O-vacancies cannot diffuse to the surface of anatase [24]. Although O-vacancies have been vastly modeled in anatase and rutile [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], to the best of the authors' knowledge, theoretical studies have not considered/compared double O-vacancy structures of rutile and anatase.…”
Section: Introductionmentioning
confidence: 99%
“…One should be aware that the symmetries may not be exact because of distortion of the atomic positions from high symmetries on account of chemical bonding. In rutile TiO 2 there is some mixing between orbitals associated with the t 2g and e g symmetries, but that is included in our theory [32,47,81]. In typical materials, such as transitionmetal oxides, the t 2g -e g splitting is on the order of eV.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The Ti-O-Ti angle is155.4º for the TiO2(A) and 130.4º and 99.1º for the TiO2(R). Shortly, by changing the substrate from STO to TiO2(A) and then to TiO2(R), we can continuously decrease the Ti-O-Ti angle, thus tune the hybridization between O2p and Ti3d eg orbitals 30.…”
mentioning
confidence: 99%